2019
DOI: 10.3389/fcimb.2019.00136
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii: CD8 T Cells Cry for CD4 Help

Abstract: Toxoplasma gondii , an apicomplexan parasite, is a pathogenic protozoan that can infect the central nervous system. In pregnant women, infection can result in congenital problems of the fetus, while in immunocompromised individual it can lead to severe neurological consequences. Although CD8 T cells play an important effector role in controlling the chronic infection, their maintenance is dependent on the critical help provided by CD4 T cells. In a recent study, we demonstrated that reactivation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 75 publications
2
33
0
Order By: Relevance
“…Accordingly, it was reported that transferring CD8 + T cells into immunodeficient mice resulted in the elimination of T gondii cysts in the brains 33 . CD4 + T‐cell exhaustion was documented to disrupt the functionality of CD8 + T cells and ultimately lead to recrudescent toxoplasmosis 34 . Consistent with these reports, fewer cyst counts were detected in the brains of mice immunized with TG146 VLP + CpG vaccine, whose CD8 + T‐cell populations were much greater than those induced by TG146 VLPs alone.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it was reported that transferring CD8 + T cells into immunodeficient mice resulted in the elimination of T gondii cysts in the brains 33 . CD4 + T‐cell exhaustion was documented to disrupt the functionality of CD8 + T cells and ultimately lead to recrudescent toxoplasmosis 34 . Consistent with these reports, fewer cyst counts were detected in the brains of mice immunized with TG146 VLP + CpG vaccine, whose CD8 + T‐cell populations were much greater than those induced by TG146 VLPs alone.…”
Section: Discussionmentioning
confidence: 99%
“…The lymphocytes role in T. gondii infection is in restriction of parasite replication during the chronic phase. Amongst the adaptive immune subsets, CD8 T lymphocytes are the primary effector cells while CD4 T cells play an essential helper function to maintain long-term immunity (Khan et al 2019 ). The action of lymphocytes in T. gondii infection starts with its activation by macrophages and dendritic cells, followed by induction of Th1 cells and antigen-specific killer CD8 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…gondii infection, such as DCs, macrophages, CD8 + and CD4 + lympocytes, granulocytes, and NK cells. In particular, CD4 + T h 1 cells, activated through interleukin 12 (IL12) stimulation from antigen-presenting cells (APCs), induce a robust CD8 + T cell effector immunity, these cells being an important source of IFNγ and also exhibiting cytotoxic activity against infected targets [ 51 , 52 ]. These principles of systemic immunity to T .…”
Section: The Immune Response To Otmentioning
confidence: 99%